A Bibliometric Analysis of Sukuk using VOSviewer in Indonesia with Publish or Perish (PoP) - Lukito, Shellvy; Firmansyah, Egi Arvian (AL-MUZARA'AH, 2024)
The subject matter of sukuk has elicited increasing attention from both academic researchers and professionals within the industry. The employment of sukuk financing is effectively facilitating the progression of economic growth. The primary objective of this research endeavor is to integrate mapping analysis techniques with the utilization of VOSviewer software to conduct a comprehensive bibliometric analysis of scholarly literature pertaining to sukuk. The acquisition of research data is facilitated through the utilization of the Publish or Perish (PoP) application. The data collected has been derived from an examination of search outcomes pertaining to the keyword "sukuk" obtained from scholarly journals indexed by Google Scholar. A total of 997 articles, spanning the period from 2018 to 2022, have been identified in the present study. Based on the research findings, it has been observed that there has been a consistent upward trend in the number of studies conducted over the period 2018 to 2022. Islamic bonds, commonly referred to as sukuk, play a pivotal role in facilitating and propelling this expansion. The present study showcases the significance of bibliometric analysis in furnishing analytical data about occurrences. This study provides guidelines and serve as a valuable resource for researchers engaged in the exploration and identification of research themes.